Tantangan dalam Penempatan Aparatur Sipil Negara (ASN) di Daerah Kabupaten Kepulauan Mentawai Provinsi Sumatera Barat - Sari Zaman Wulandari; Raudhatul Jannah; M. Thfeil Arabbi; Yulia Hanoselina (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
The placement of Civil Servants (ASN) in the Mentawai Islands Regency, West Sumatra Province, faces significant challenges, such as difficult transportation access, limited communication networks, and budget constraints for improving ASN competency. This study aims to analyze these challenges and their impact on public services in remote areas. The research method used is a literature review, gathering data from various related sources. The findings show that ASN in the Mentawai Islands often face long and costly journeys to attend training due to limited sea transportation. Inadequate communication networks hinder the ASN's duties and efforts to improve education quality. Budget limitations for training and competency development also pose challenges, negatively affecting discipline and the quality of public services. The remoteness of the area and its vulnerability to disasters are additional concerns for ASN, and the lack of infrastructure hampers their activities. Therefore, better management strategies for ASN in remote areas are needed to enhance the effectiveness of public services and support the development of policies that are more responsive to the needs of the local community.